National Archives knew that victims were in files of potential Nazi collaborators in WW2 - NL Times (Netherlands Times, 2025)
The National Archives already knew last year that the names of innocents or even victims appear in a sensitive archive with files about Dutch people who were accused of collaborating with the German forces during the Second World War. Yet the institution only published a warning after the media reported on this, NU.nl reported.